Macrophage activation of the TREM2-DAP12-SYK pathway shapes the adipose tissue microenvironment in obesity and unveils the therapeutic potential of natural compounds egcg and SMRR - Luoying, Wang; Xingcheng, Yi; Donghang, Cong; Mengtuan, Long; Ping, Wang; Lijuan, Zhang; Yupeng, Li; Tianyi, Zhao; Hongyu, Chen; Song, Wang; Zijun, Zang; Hanyu, Zheng; et al. (Frontiers in Immunology, 2025)
Obesity is a major global health burden, with current therapies limited by metabolic adaptation and adverse effects. Although transcriptomic studies reveal widespread gene alterations in obesity, key drivers and their cell-specific origins in adipose tissue remain unclear. Defining these regulators is critical for understanding immune-metabolic imbalance and developing targeted interventions. We integrated bulk transcriptomics (n=434) with single-cell RNA-seq (194,608 cells from 24 adipose samples) to identify BMI-associated gene modules and macrophage regulatory programs. Cell-specific networks, subtype-specific gene regulatory networks, pseudotime trajectories, and cell–cell communication analyses delineated macrophage heterogeneity. Molecular docking assessed interactions between candidate drugs and the TREM2–DAP12–SYK pathway, and in vivo studies evaluated the therapeutic potential of EGCG and SMRR in high-fat diet mice. Our analyses revealed significant molecular and microenvironmental differences between healthy and obese adipose tissue. Eight BMI-associated genes—SYK, CD86, CSF1R, HCK, TYROBP, LAPTM5, ITGB2, and ACTB—were predominantly expressed in macrophages. Single-cell profiling identified macrophage subtypes (C4, C6, C10) with distinct regulatory roles in adipocyte communication. Dysfunction of the TREM2–DAP12–SYK axis underpinned obesity-associated macrophage states, while EGCG and SMRR reactivated this pathway, mitigating obesity and metabolic dysfunction in vivo. These findings define a macrophage-centered regulatory network driving obesity progression and highlight actionable therapeutic targets.